KARAKTERISTIK MUTU FISIKOKIMIA DAN ORGANOLEPTIK TEH KULIT KOPI (CASCARA) DENGAN PENAMBAHAN LEMON DAN MADU - Murna Muzaifa; Syarifah Rohaya; Hilyati Ainia Sofyan (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Cascara is coffee husk that has been dried and drunk like tea through a brewing process. This study aims to improve the taste of cascara tea which is still unfamiliar in Indonesia by adding lemon and honey. The study used lemon extract (L) with different concentrations of 0.5% and 1%. Honey (P) used also varied with concentrations of 5%, 10%, 15%. The analysis carried out on the cascara drink was physicochemical analysis (antioxidant activity, total Vitamin C, pH) and sensory analysis (hedonic test on taste, color and aroma). The results showed that the concentration of lemon extract affected antioxidant activity, Vitamin C, pH, taste and aroma of cascara tea. The higher the concentration of lemon used, the higher the antioxidant activity, vitamin C, and the pH of cascara tea. honey concentration affects the pH value and taste of cascara tea. The higher the concentration of honey used, the lower the pH value of cascara tea but it can increase the panelists' favorites for the taste of cascara tea. Based on the chemical and organoleptic characteristics, the best treatment was obtained by adding 1% lemon and 7.5% honey.